Progressive Vaccinia Acquired through Zoonotic Transmission in a Patient with HIV/AIDS, Colombia (2020)
In March 2015, a patient in Colombia with HIV/AIDS was hospitalized for disseminated ulcers after milking cows that had vesicular lesions on their udders. Vaccinia virus was detected, and the case met criteria for progressive vaccinia acquired by zoonotic transmission. Adherence to an optimized antiretroviral regimen resulted in recovery.